Effect of partial replacement of coarse aggregate by polystyrene balls on the shear behaviour of deep beams with web openings. (June 2020) - Shaaban, Ibrahim G.; Zaher, Amr H.; Said, Mohamed; Montaser, Wael; Ramadan, Mohamed; Abd Elhameed, Ghada N.
Highlights: Size and location of the web openings has a major impact on the failure mode and ultimate shear strength of reinforced LWC deep beams. Finite element predictions for load-carrying capacities, cracking pattern and load-deflection relationships, were very good. It is recommended that the depth of opening should not exceed 20% of the total depth of the deep beam. In the case of opening depth larger than 20% of the beam depth, internal strengthening around its perimeter is essential. Strut-and-tie model was used successfully for predicting deep beams containing polystyrene balls as coarse aggregates. Abstract: Thirteen specimens were experimentally tested under single midspan concentrated loads to study the shear behavior of lightweight concrete (LWC) and normal weight concrete (NWC) deep beams with web openings. In this research, the term LWC refers to the concrete obtained by partially replacing aggregate by polystyrene foam balls not the concrete containing lightweight aggregate. This resulted in a weight reduction of LWC beams in this research by approximately 30% compared to NWC compartments. The studied variables were the dimensions and location of openings, transverse reinforcement ratio, and shear span to depth ratio (a/d). It was found that the overall shear behavior and failure mode for LWC deep beams are comparable to those of the NWC specimens. This is very promising and encouraging to build lighter deep beams of similar structural behaviour as that of NWC deep beams. Dimensions of the openings have a significant effect on the behaviour of failure and shear strength of LWC and NWC deep beams. It was found that increasing the depth of the opening from 20 % to 40 % of the beam depth led to a reduction in the ultimate load by up to 46.4 %. Finite element modelling of the test beams was carried out to verify numerical results versus experimental work and both were very well correlated. In addition, a parametric study was conducted to assess the effect of internal stiffening around openings in deep beams. The maximum enhancement in the shear capacity was approximately 30 % for beams, internally strengthened by additional reinforcement on the perimeter of openings compared to the beams without any reinforcement around the openings. Strut-and-Tie model (STM) was carried out as a rational approach to predict the shear behaviour of studied beams. It was found that STM underestimates the shear of the studied beams compared to experimental results for different tested beams but the agreement between both of them was acceptable. It is recommended that the depth of opening should not exceed 20 % of the depth of the deep beam and if the depth of opening is more than that or lies in the shear span it is highly recommended to strengthen the opening internally by additional reinforcement around its perimeter.